2018
DOI: 10.1111/nyas.13687
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic adaptation of short‐living growth hormone transgenic mice to methionine restriction and supplementation

Abstract: Extension of mammalian health and life span has been achieved using various dietary interventions. We previously reported that restricting dietary methionine (MET) content extends life span only when growth hormone signaling is intact (no life span increase in GH deficiency or GH resistance). To understand the metabolic responses of altered dietary MET in the context of accelerated aging (high GH), the current study evaluated MET and related pathways in short-living GH transgenic (GH Tg) and wild-type mice fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 78 publications
(99 reference statements)
1
12
1
Order By: Relevance
“…Previous reports showed that 80% MetR increases the level of GSH in erythrocytes in rats [ 7 , 64 ]. Although MetR decreases the GSH levels in several tissues, including the liver [ 7 , 64 , 65 , 66 , 67 , 68 , 69 ], oxidative stress is not enhanced. The low levels of hepatic GSH induced by MetR are compensated by increased antioxidative capacity, including increased erythroid 2-like 2 transcription factor (NFE2L2)-induced antioxidative responses [ 65 ].…”
Section: Mechanisms Underlying the Roles Of Metr In Lifespan Extenmentioning
confidence: 99%
“…Previous reports showed that 80% MetR increases the level of GSH in erythrocytes in rats [ 7 , 64 ]. Although MetR decreases the GSH levels in several tissues, including the liver [ 7 , 64 , 65 , 66 , 67 , 68 , 69 ], oxidative stress is not enhanced. The low levels of hepatic GSH induced by MetR are compensated by increased antioxidative capacity, including increased erythroid 2-like 2 transcription factor (NFE2L2)-induced antioxidative responses [ 65 ].…”
Section: Mechanisms Underlying the Roles Of Metr In Lifespan Extenmentioning
confidence: 99%
“…Indeed, unpublished studies from the Orentreich Foundation found that GH injections abrogate the MR phenotype of methionine-restricted rats (not shown). In addition, Brown-Borg et al recently demonstrated that short-lived GH-overexpressing transgenic mice show an impaired response to MR ( Brown-Borg et al, 2018 ). Accordingly, we hypothesized that any intervention that reduces IGF-1 levels (or otherwise impairs IGF-1 signaling) will produce MR-like healthspan benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the SAM:SAH ratio is markedly increased, while liver and kidney gnmt mRNA levels are decreased in the short-lived growth hormone transgenic mice (GH-Tg). Methionine restriction reverses the SAM:SAH ratio in GH-Tgs but not to wt levels [ 118 ]. In flies, genetic suppression of two out of three AHCY homologs, systemically or in a tissue-specific manner, reduces age-related SAH accumulation and leads to lifespan extension [ 80 ].…”
Section: One-carbon Metabolism In Agingmentioning
confidence: 99%